Empowerment of Retired Citizens with The Utilization of Used Tires as A Street Bump: Pemberdayaan Warga Purna Tugas Dengan Pemanfaatan Ban Bekas sebagai Street Bump - Ellyta, Ellyta; Widarti, Sri; Youlla, Donna (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
Densely populated settlements experience a classic problem in terms of transportation, namely the speed of vehicles. The problem faced by residents is the risk of danger by residents due to motorists and cars crossing the road at high vehicle speeds. This service aims to increase partners' knowledge and provide skills for retired residents to use used tires to reduce vehicle speed. The implementation method involves the full participation of the community. Activities carried out with lectures, discussions, and demonstrations. Community Service Activities' findings have increased partners' knowledge by 90%. In addition, there are also social impacts in the form of a sense of security and comfort for residents. This can be seen from the addition of the installation of speed bumps from used tires with self-help funds and self-help workers. Full participation from partners from planning to activity evaluation shows that this activity positively impacts the community. Abstrak Pemukiman padat penduduk mengalami masalah klasik dalam hal transportasi yaitu kecepatan kendaraan yang melintas. Permasalahan yang dihadapi Warga RT 003 RW 020 Jalan Nawawi Hasan 1 Perumnas 2 Kelurahan Sungai Beliung adalah resiko bahaya yang dialami warga akibat pengendara baik motor maupun mobil yang melintasi jalan tersebut dengan kecepatan kendaraan tinggi. Tujuan dari pengabdian ini adalah untuk menambah pengetahuan mitra dan memberikan keterampilan untuk warga purna tugas memanfaatkan ban bekas untuk mengurangi laju kendaraan. Metode pelaksanaan dengan melibatkan partisipasi penuh masyarakat. Kegiatan dilaksanakan dengan cermah, diskusi, dan demonstrasi. Temuan dari Kegiatan Pengabdian Kepada Masyarakat terjadi peningkatan pengetahuan kepada mitra sebesar 90%. Selain itu terjadi pula dampak sosial berupa rasa keamanan dan kenyamanan warga. Hal ini dapat dilihat dari penambahan pemasangan polisi tidur dari ban bekas dengan dana swadaya dan tenaga swakarya. Partisipasi penuh dari mitra baik dari perencanaan sampai dengan evaluasi kegiatan menunjukkan kegiatan ini memberikan dampak positif bagi masyarakat.